Resíduo de porongo como componente de substrato para a produção de alface - Onhinam, Siozimila Fernandes (2025)
Organic waste management is a challenge in agricultural activity. Many residues lack information for agricultural use, such as residue from the production of bottle gourds and crop residues. The objective of this study was to evaluate whether the use of calabash residue and vermicompost in the composition of substrate favors the production of lettuce seedlings and plants. Two experiments were carried out with calabash residues with two particle sizes (0.5 and 1.0 cm), vermicompost, vermiculite and commercial substrate. Veneranda curly lettuce cultivar was used. The seedling height, number of leaves, root length, chlorophyll index, fresh mass of the aerial part and fresh mass of the root, and formation of the seedling clod were evaluated. The same evaluations were performed for the lettuce plant, except for the formation of the root clod. For the production of seedlings, the substrate with a composition of 20% of calabash residue with a particle size of 0.5 cm together with 80% of vermicompost, proved to be effective as an alternative substrate, presenting good averages in root clod structure, plant height and number of leaves for seedlings with 14, 21 and 28 days. For the production of lettuce plants, the use of 20% vermiculite with 80% of vermicompost favors the development and production of the lettuce cultivar Veneranda. The use of residues from the production of calabash can help in the economic gain for the producers of bottle gourd since, during the gourd production process, more than 60% of lhe bottle gourd is discarded, becoming an environmental problem.